2017
DOI: 10.1016/j.jcrimjus.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of murderers with recidivists and first time incarcerated offenders from U.S. prisons on psychopathy and identity as a criminal: An exploratory analysis

Abstract: Previous research conceptualized murderers as highly callous and self-gratifying individuals, offending as a result of psychopathic tendencies. The current exploration sought to verify whether murderers differ on psychopathy and criminal social identity from recidivistic and first time incarcerated offenders. Methods: The study compared an opportunistic sample of murderers (n = 94), recidivists (n = 266), and first time offenders (n = 118) on criminal social identity (3 factors: cognitive centrality, in-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
10
0
6
Order By: Relevance
“…Taking into account the components of the profile, and if we assume that having a partner has a status analogous to marriage in this population, the tendency of these individuals to have fewer criminal records can be explained. Within the various results provided by the literature, the remainder of our findings are consistent with those that suggest that murderers do not present more psychopathic characteristics and aggressiveness than other offenders [ 6 , 11 , 52 ]. Finally, although substance abuse is highly prevalent throughout the prison population [ 34 , 53 ], this problem does not appear to be one of the main characteristics of the killers.…”
Section: Discussionsupporting
confidence: 91%
“…Taking into account the components of the profile, and if we assume that having a partner has a status analogous to marriage in this population, the tendency of these individuals to have fewer criminal records can be explained. Within the various results provided by the literature, the remainder of our findings are consistent with those that suggest that murderers do not present more psychopathic characteristics and aggressiveness than other offenders [ 6 , 11 , 52 ]. Finally, although substance abuse is highly prevalent throughout the prison population [ 34 , 53 ], this problem does not appear to be one of the main characteristics of the killers.…”
Section: Discussionsupporting
confidence: 91%
“…Recently research has found evidence of the importance of social relationships and ties with criminal others in the perpetration of violence Sherretts & Willmott, 2016), however these social factors were significantly less important determinants of offence perpetration in homicide inmates, than other offender groups (Sherretts, Boduszek, Debowska & Willmott, 2017). For behaviourists a fundamental criticism of psychodynamic perspectives, including Neo-Freudian object relations theory, is the degree of emphasis attributed to childhood experiences and caregiver influences, which as a consequence negates seemingly significant adult experiences and environmental factors in the commission of behaviour (Hale, 1993;Castle & Hensley, 2002).…”
Section: Competing Explanationsmentioning
confidence: 98%
“…Postojanje deprivacija u zatvorima doprinosi i viktimizaciji osuđenih. Činjenica je da se u zatvorima nalaze različite kategorije prestupnika, učinilaca lakših i težih krivičnih dela, neretko sa agresivnim ili psihopatskim osobinama, recidivisti i primarno zatvarani, sa različitim stepenom rizika recidivizma i rizika po sopstvenu i bezbednost drugih (Sherretts, Boduszek, Debowska & Willmott, 2017).…”
Section: Uvodunclassified